New equations to determine exercise intensity using different exercise modes - Martins, R. A.; João Coelho e Silva, M.; Sardinha, L. B. (Biology of Sport, 2012)
The purpose of this study was to determine new equations from the relationship of % ·VO2max versus %HRmax, based on direct measures of oxygen uptake, in four exercise modes (leg cycling, rowing, stepping and running), in young adult females and males with low risk for cardiovascular disease. Ten adult males and ten females volunteered for the study. The participants performed an incremental test for each exercise mode until exhaustion. Regression analyses were carried out for each participant at a target % of VO2max and %HRmax was computed. At 40-90% ·VO2max, the regression equations predicted similar values of %HRmax for males and females in the four exercise modes. In contrast, estimated %HRmax for cycling was higher at 40-70% ·VO2max, when compared with stepping and running. The results support the notion that a single equation to predict target heart rate values for both males and females can be applied. Furthermore, at light and moderate intensities, leg cycling produces different % ·VO2max-%HRmax regression equations than stepping and running.